Industrial training report: Perpustakaan Tengku Anis / Syahril Ulya - Ulya, Syahril (Perpustakaan Tengku Anis, 2023)
The internship programme at Tengku Anis Library, Machang UiTM Cawangan Kelantan took place from April to 31 July 2023. Through internship activities, students implement and apply various theories and learning that have been received in the classroom to gain direct experience and insight in the work environment. The purpose of internship activities is to gain practical experience from the internship site by applying the knowledge that has been learned and honing skills to face a challenging work environment. During the internship, students are assigned to all library departments including administrative department, library service department, university reference department, digital library, and university archive department. Moreover, trainees also had special projects such as CSR Vitamin Ilmu SMK Pangkal Meleret, CSR Jalinan Kasih with Orphans, participating in GSISS 2023, conducting interviews, and creating an online exhibition with a cultural theme from Indonesia. Various experiences have been gained from the internship programme both from specific experience in the library field or soft skills that continue to be developed. In the end, the experiences and insights gained during the internship are expected to continue to be developed and can be of value to the internship site and of course the trainees for self-development.